A study of relationship of debt ratio, return on asset & return on equity on TNB financial efficiency / Khadijah Mohd Affendi - Mohd Affendi, Khadijah (2011)
The purpose of this paper is to study of relationship of debt ratio, return on asset and return on equity on TNB financial efficiency. Three ratio are used in determine the financial efficiency . The first objective is researcher want to study on determinants of TNB financial efficiency, second is to identify the relationship between profit of the company with independent variables (debt ratio, return on asset, return on equity) and third is to give the suggestion how to improve the efficiency at TNB’s management. The data was get from secondary data which is from the company annual report about 10 years and also get from informal interview by top management of TNB Tanah Merah. The Statistical Procedure of Social System (SPSS) are used in key in the data. From this program multiple linear regressions, correlation of coefficient (R), coefficient of determination (R²), Durbin Watson, and T- statistic are used in analysis. All the data are used in yearly from year 2001 to year 2010. This result indicates that all variables are having significant relationship with the dependent variable which are debt ratio, return on asset, and return on equity